1996
DOI: 10.1128/iai.64.1.146-153.1996
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane protein A of Escherichia coli contributes to invasion of brain microvascular endothelial cells

Abstract: Escherichia coli is the most common gram-negative bacteria causing meningitis during the neonatal period, but it is unclear what microbial factors mediate traversal of E. coli across the blood-brain barrier. Outer membrane protein A (OmpA), a highly conserved 35-kDa protein, was examined for its role in E. coli K1 invasion of brain microvascular endothelial cells (BMEC). The invasive capability of the OmpA ؉ strains was 25-to 50-fold greater than that of OmpA ؊ strains, and the invasive capability of OmpA ؊ st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(190 citation statements)
references
References 41 publications
7
179
2
2
Order By: Relevance
“…Third, E. coli stimulates the tyrosine phosphorylation of endothelial cell proteins and is endocytosed after 10-20 min of infection (Prasadarao et al, 1997;, compared with C. albicans which induces tyrosine phosphorylation and its own endocytosis only after 60 min of contact with the endothelial cells. Finally, the uptake of E. coli by brain microvascular endothelial cells is associated with the tyrosine phosphorylation of a MAP kinase (Prasadarao et al, 1997). Candida albicans did not induce any detectable phosphorylation of MAP kinases, which would have been discernible in the Triton X-100 soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Third, E. coli stimulates the tyrosine phosphorylation of endothelial cell proteins and is endocytosed after 10-20 min of infection (Prasadarao et al, 1997;, compared with C. albicans which induces tyrosine phosphorylation and its own endocytosis only after 60 min of contact with the endothelial cells. Finally, the uptake of E. coli by brain microvascular endothelial cells is associated with the tyrosine phosphorylation of a MAP kinase (Prasadarao et al, 1997). Candida albicans did not induce any detectable phosphorylation of MAP kinases, which would have been discernible in the Triton X-100 soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous observations showed that actin polymerization is necessary for OmpA+ E. coli to invade HBMEC (Prasadarao et al, 1996). Therefore, to examine the possible role of IQGAP1 in actin remodelling, HBMEC were infected with OmpA+ E. coli and examined for actin and IQGAP1 localization using rhodamine-phalloidin and antimyc antibody, respectively at different time points.…”
Section: Iqgap1 Expression Is Important For E Coli K1 Invasion Into mentioning
confidence: 99%
“…Escherichia coli E44, a rifampin-resistant mutant of E. coli K1 strain RS 218 (serotype O18:K1:H7), was previously isolated from the cerebrospinal fluid of a neonate with meningitis and invades HBMEC. E91, a derivative of E44 in which the ompA gene was disrupted by allelic exchange, has been described earlier (Prasadarao et al, 1996). All bacteria were grown in Luria-Bertani broth with appropriate antibiotics.…”
Section: Bacteria Antibodies and Other Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E. coli strains E44 (OmpA+) and E91 (OmpA-) used in this study are derivatives of the E. coli K1 strain RS218 (serotype 018 : K1 : H7) (Prasadarao et al, 1996a). Strain E44 is a spontaneous rifampicin-resistant mutant and invades HBMEC.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%